Typology of discourse coalition networks and actors in the coverage of electric vehicles on Tempo.co and Kompas.com - Fadhilah, Nadia Ayu; Ahmad, Nyarwi (Universitas Bunda Mulia, 2025)
Since 2019, the Jokowi government has implemented policies on electric vehicles (EVs) to reduce greenhouse gas emissions. While controversial, these policies generated diverse responses and spurred multiple discourses, which were widely reported in mainstream media. Based on Talkwalker data, Tempo.co and Kompas.com were selected for analysis as both consistently covered EV issues in 2023. This article examines the types of actors and discourse coalition networks that emerged in the EV debates reported by Tempo.co and Kompas.com. To do so, the discourse and discourse coalition theories, mediation theory, and Discourse Network Analysis (DNA) method were adopted. Data from 194 news articles collected through observation and documentation during May 7–14 and May 20–27, 2023, were coded using an established framework, analyzed with Visone software, and qualitatively interpreted. The findings reveal pro, contra, and evaluative discourse coalition networks in Tempo.co and Kompas.com. The government successfully identified all dominant actors in the first phase but failed in the second phase. In the second phase, researchers became dominant actors in Tempo’s reporting, with discourses largely focused on criticism and evaluation of EVs. The data shows that the Central Government failed to anticipate the discourse that developed in the media. In addition, the difference in the selection of actors and discourses shows the powers of the mediation processes carried out by each medium. This study contributes to DNA analysis by separating results based on media sources and confirms the role of dominant actors in shaping the electric vehicle discourse.